2004
DOI: 10.1007/s00705-003-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity of the coat protein-encoding region of Barley yellow dwarf virus-PAV and Barley yellow dwarf virus-MAV from Latvia and Sweden

Abstract: The sequence variability of Barley yellow dwarf virus-PAV (PAV) and Barley yellow dwarf virus-MAV (MAV) was studied by comparing 502 nucleotides from the coat protein-encoding region of six isolates from Latvia and four from Sweden. The diversity within MAV was low (>97% sequence identity), also when compared to isolates from USA and China. In contrast, the variability among PAV isolates was greater and phylogenetic analysis including isolates of a wide geographic origin detected two major clusters, of which b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
3
32
1
Order By: Relevance
“…Similar detection problems involving large numbers of symptomatic plants did not occur on other sites in the Matanuska Valley, where infections by BYDV-PAV and CYDV-RPV were readily confirmed by ELISA and RT-PCR [23]. Bisnieks [1] reported successful detection and amplification of the CP gene for BYDV-PAV and CYDV-RPV, and not isolates of BYDV-MAV, using immunocapture RT-PCR with the appropriate antiserum and the universal luteovirus primers. They subsequently incorporated a specific primer set for successful BYDV-MAV amplification and analysis.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Similar detection problems involving large numbers of symptomatic plants did not occur on other sites in the Matanuska Valley, where infections by BYDV-PAV and CYDV-RPV were readily confirmed by ELISA and RT-PCR [23]. Bisnieks [1] reported successful detection and amplification of the CP gene for BYDV-PAV and CYDV-RPV, and not isolates of BYDV-MAV, using immunocapture RT-PCR with the appropriate antiserum and the universal luteovirus primers. They subsequently incorporated a specific primer set for successful BYDV-MAV amplification and analysis.…”
Section: Discussionmentioning
confidence: 72%
“…Upon examination of the nucleotide sequences in the AK BYDV-MAV-like isolates and available sequences for BYDV-MAV from data banks, the suitability and application of the various primers designed by different researchers for detection became evident. Firstly, the universal Lu 1 primer, 5 -CCAGTGGTTRT GGTC-3 , was not useable for detection for any BYDV-MAV [1,15,17], including the AK BYDV-MAV-like isolates, since there was no sequence counterpart in the coat protein region, with a specific mismatch in the equivalent region, Novel Alaska barley yellow dwarf virus 379 5 -ACAGTGGTTATGGCA-3 . Interestingly, if BYDV-MAV sequence information had been available for the original design of the universal luteovirus primers [25], Lu 1 probably would not have been formulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In northern Europe, where climatic conditions are similar to the long photoperiods and relatively cooler temperatures of Alaska's growing season, Bisnieks et al [2] reported six PAV isolates from Sweden (PAV Sweden, PAV Storvreta) and Latvia (PAV Saldus 1, -2, PAV Priekuli 1, -2) that were similar to each other (except a distinct variant, PAV Saldus 1). The five Alaska PAV isolates from Fairbanks formed a separate cluster that associated with these Swedish=Latvia isolates, and not the PAS isolates from Palmer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The PAV and PAS species analyzed in this study are ecologically similar, sharing the same aphid vectors (Rhopalosiphum padi and Sitobion avenae) (Chay et al, 1996) and host species (many members of the family Poacea). PAV and PAS have approximately 90% and 78% nucleotide sequence identity in their capsid protein (Bisnieks et al, 2004) and polymerase genes (Hall, 2006), respectively. The effect of one virus species on the population growth of the other during mixed infections has not yet been reported, but plants infected with both species have been identified in natural plant populations in France (Mastari et al, 1998) and New York State (Hall, 2007).…”
Section: Introductionmentioning
confidence: 99%